COVID-associated panic attacks: regional management aspect - Moroz, Svitlana; Khozhylo, Iryna; Ryzhenko, Sergii; Semenikhina, Vladlena; Turishcheva, Nataliia; Khaitov, Roman (My University, 2020)
The modern coronavirus pandemic (COVID-19) poses a mortal threat to the populations of more than 210 countries and at the same time constitutes a real challenge to national governments. One of the pandemic problems is the fear of uncertainty, which may lead to development of panic attacks among the general population. It was established that at the national level in Ukraine, standards for provision of medical care to patients with panic attacks amid the COVID-19 pandemic have not been elaborated. The article analyses measures of regional authorities on creating an algorithm for providing the special care to patients with mental disorders during a pandemic on the basis of a specialized psychosomatic clinic.
Keywords: mental disorders; СOVID-19; medical care; algorithm; health management